Performance Evaluation of Routing Protocols in Enterprise Networks - Mwewa, Webby; Lubobya, Smart C (American Journal of Computing and Engineering, 2022)
This paper evaluates the performance of routing protocols such as OSPF, EIGRP and IS-IS in an enterprise network. Routing protocols are rules that govern the best route to transfer data between various nodes in networks. These rules are used in the transmission of information from the transmitting end to the receiving end. Routing protocol's main responsibility lies in determining the best way routers communicate with each other in order to forward any kind of network traffic using the optimal path. The evaluation of routing protocols was achieved by measuring packet end-to-end delay, packet delay variation, Jitter, Ethernet delay, traffic sent and received parameters by employing OPNET simulator software using Http, Video conferencing and Voice data types. The results shows that OSPF_IS-IS combined protocols outperforms the of OSPF_EIGRP and OSPF protocols by 60%.